Insider threat protecting the enterprise from sabotage, spying, and theft - Cole, Eric (Syngress Elsevier Science [distributor], 2006)
Teaches IT professionals and law enforcement officials about the dangers posed by insiders to their IT infrastructure, and how to mitigate these risks by designing and implementing secure IT systems, as well as security and human resource policies. The authors use their backgrounds in the CIA to analyze several cases involving insider threats